2017
DOI: 10.1002/aoc.4061
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles immobilized onto poly(4‐vinylpyridine)‐functionalized magnetic nanoparticles: A robust magnetically recyclable catalyst for oxidant‐free alcohol dehydrogenation

Abstract: A heterogeneous and recyclable catalyst with a high loading of silver nanoparticles was synthesized via the silver nanoparticles being supported onto the surface of magnetic nanoparticles coated with poly(4‐vinylpyridine). The synthesized catalyst was used in the dehydrogenation of alcohols to corresponding carbonyl compounds. A broad diversity of alcohols was converted into their corresponding carbonyl compounds in excellent yields. The catalyst was easily recovered by applying an external magnetic field and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Another example of grafting of the P4VP brush was reported by Bayat et al 78 The authors synthesized Ag NPs stabilized by P4VP on the surface of magnetic NPs using multiple modification steps such as the formation of Fe 3 O 4 NPs, coating with silica, functionalization with thiol groups, grafting of P4VP, coordinating a Ag compound, and reduction with NaBH 4 . The catalyst showed excellent properties in dehydrogenation of various alcohols to corresponding carbonyl compounds with high conversion, selectivity, and exceptionally high TOF, but it is unclear whether a multistep procedure of the catalyst fabrication could be simplified to achieve the same enhancement of the catalytic performance and reusability.…”
Section: Thin Films and Grafted Polymer Layersmentioning
confidence: 99%
“…Another example of grafting of the P4VP brush was reported by Bayat et al 78 The authors synthesized Ag NPs stabilized by P4VP on the surface of magnetic NPs using multiple modification steps such as the formation of Fe 3 O 4 NPs, coating with silica, functionalization with thiol groups, grafting of P4VP, coordinating a Ag compound, and reduction with NaBH 4 . The catalyst showed excellent properties in dehydrogenation of various alcohols to corresponding carbonyl compounds with high conversion, selectivity, and exceptionally high TOF, but it is unclear whether a multistep procedure of the catalyst fabrication could be simplified to achieve the same enhancement of the catalytic performance and reusability.…”
Section: Thin Films and Grafted Polymer Layersmentioning
confidence: 99%
“…In addition, the catalytic activity of NH-Pd(0)@MNP was compared with other catalysts in the dehydrogenation condensation of benzyl alcohol reported in literature. [2,8,9,[22][23][24][25][26][27] Base was needed when Ag/ZnO and PVP-Ru were used as catalysts (Table 2, entries 6, 7). Other catalysts required either longer time or higher temperature ( Table 2, entries 8-14).…”
Section: Resultsmentioning
confidence: 99%
“…Dehydrogenation of primary and secondary alcohols to carbonyl compounds is of great value in organic synthesis and the products are also versatile organic compounds. [1][2][3][4][5][6] The metal-based oxidants such as potassium permanganate, chromium reagents, osmium reagents, or ruthenium reagents are traditionally used in most of the oxidative dehydrogenations. However, these methods have the disadvantages of high cost, low selectivity and large amount of waste.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that as recyclable heterogeneous catalyst, silver-based nanoparticles have high conversion and selectivity in alcohol oxidation or crosscoupling. [19][20][21][22] In order to improve the catalytic ability and recyclability of silver catalysts, many materials (hydrogel, cellulose, carbon fibers, magnetic materials, etc.) have been developed to support Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 99%